1996
DOI: 10.1172/jci118378
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin II in dietary modulation of rat late distal tubule bicarbonate flux in vivo.

Abstract: We have reported that overnight fasting stimulates bicarbonate reabsorption (J tCO2 ) in rat distal tubules. The present in vivo microperfusion studies evaluated the hypothesis that endogenous angiotensin II (AII) mediates this response. Rat late distal (LD) tubules were perfused at 8 nl/min in vivo with a hypotonic solution containing 28 mM bicarbonate. In overnight-fasted rats, LD J tCO2 was significantly higher than in normally fed rats (50 Ϯ 4 vs. 16 Ϯ 6 pmol/min и mm, P Ͻ 0.05). When overnight-fasted rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…13 The view that ␣ENaC abundance is regulated via AT 1 receptor occupation has derived additional support from a previous study in which ablation of the AT 1a receptor gene in mice resulted in a marked decrease in ␣ENaC protein abundance despite an increase in circulating aldosterone levels. 28 These data add to evidence from micropuncture studies 6,31,32 and patch clamp studies of isolated collecting ducts 33 that angiotensin II has the direct effect of regulating ion transport in the connecting tubule and collecting duct. Additionally, immunohistochemical studies 34 and RT-PCR studies 35 have provided evidence for expression of AT 1 receptors in collecting duct.…”
Section: Discussionmentioning
confidence: 77%
“…13 The view that ␣ENaC abundance is regulated via AT 1 receptor occupation has derived additional support from a previous study in which ablation of the AT 1a receptor gene in mice resulted in a marked decrease in ␣ENaC protein abundance despite an increase in circulating aldosterone levels. 28 These data add to evidence from micropuncture studies 6,31,32 and patch clamp studies of isolated collecting ducts 33 that angiotensin II has the direct effect of regulating ion transport in the connecting tubule and collecting duct. Additionally, immunohistochemical studies 34 and RT-PCR studies 35 have provided evidence for expression of AT 1 receptors in collecting duct.…”
Section: Discussionmentioning
confidence: 77%
“…The presence of angiotensin II type 1 (AT 1 ) receptors in the luminal and basolateral membranes of DCT epithelia offers a potential role for ANG II to directly regulate the DCT sodium transport (10, 25). ANG II has been shown to stimulate transport of bicarbonate, fluid, and sodium in the DCT (34), and proliferation of the DCT in an ANG II-mediated renal injury model (19,20). Additionally, chronic treatment with the AT 1 receptor antagonist candesartan together with vasopressin decreased NCC abundance compared with control or treatment with vasopressin alone (15).…”
mentioning
confidence: 99%
“…Studies have reported that AngII can alter transport in distal tubular segments (7,8), cortical collecting ducts (9), and macula densa cells (10,11). In the distal tubule and cortical collecting duct, AngII may stimulate Na:H exchange (7)(8)(9).…”
mentioning
confidence: 99%
“…Studies have reported that AngII can alter transport in distal tubular segments (7,8), cortical collecting ducts (9), and macula densa cells (10,11). In the distal tubule and cortical collecting duct, AngII may stimulate Na:H exchange (7)(8)(9). Also of potential importance is the findings by Wang and Giebisch (12) that the effects of AngII to stimulate volume reabsorption in the late distal tubule not only involves the acid base transporters (Na:H exchange and NaHCO 3 cotransport) but may act via Na ϩ channels.…”
mentioning
confidence: 99%